Shallow Seismicity and the Classification of Structures in the Lau Back‐Arc Basin. (15th July 2020) - Baxter, A. T.; Hannington, M. D.; Stewart, M. S.; Emberley, J. M.; Breker, K.; Krätschell, A.; Petersen, S.; Brandl, P. A.; Klischies, M.; Mensing, R.; Anderson, M. O.
Abstract: Back‐arc basins open in response to subduction processes, which cause extension in the upper plate, usually along trench‐parallel spreading axes. However, global seismic databases reveal that the majority of seismic events in the Lau Basin occur along transcurrent (strike‐slip) rather than extensional faults. To better characterize active deformation in this region, we compared centroid moment tensors (CMTs), calculated for large (Mw > 5), shallow (<30 km) seismic events, to the orientations of seafloor lineaments mapped throughout the Lau Basin. Ship‐based multibeam and satellite altimetry were combined with vertical gravity gradient data to create the lineament map. By comparing the possible focal planes of the CMTs to the orientations of the lineaments, the most likely fault plane solutions were selected, thus classifying the faults and establishing the nature of the highly variable stress regimes in the basin. We resolved the strike, dip, and dip direction of 308 faults and classified 258 additional structures by fault type. The analysis highlights a stress regime that is dominated by a combination of left‐lateral and right‐lateral strike‐slip faults, large‐scale transcurrent motion along rigid crustal‐scale fault zones, and nonrigid diffuse deformation along preexisting seafloor structures, with extension mainly limited to the tips of propagating rifts and spreading centers. By resolving many of the uncertain motions on the mapped lineaments of the Lau Basin, the CMT analysis addresses a number of questions concerning basin‐scale stress regimes and microplate development, complementing GPS measurements, and providing a more complete picture of the complexities of back‐arc basin development. Plain Language Summary: The tectonics of back‐arc basins are commonly viewed as a response to rollback of a subducting slab beneath a volcanic arc, with basin opening caused by simple rifting and accretion at a back‐arc spreading center. However, detailed analysis of seismicity in the Lau Basin shows a much more complicated history of evolving stress regimes and deformation, with unexpectedly few recently active extensional faults. Instead, both rigid and nonrigid deformation are dominated by strike‐slip faulting in response to strong curvature of the trench and widespread microplate and block rotation. The resulting pattern of deformation has significant implications for large‐scale crustal permeability and the distribution of magmatic and hydrothermal systems. Key Points: Centroid moment tensors, calculated for large, shallow seismic events, were compared to seafloor lineaments mapped throughout the Lau Basin The most likely fault plane solutions were chosen, thus classifying the faults and establishing the nature of the basin's stress regimes Stress regimes are highly variable but dominated by both rigid and nonrigid transcurrent deformation, and extension at spreading centers